PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR MATRIKS (Studi Kasus pada Siswa Kelas X-G Program Keahlian RPL SMK Senopati Sedati Sidoarjo) - Sumiati, Sumiati; Sumartono, Sumartono (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2017)
This research was motivated by the low result of learning mathematics SMK SMK Senopati Sedati Sidoarjo, with formulation of the problem is: is there any influence of cooperative learning model type Teams Games Tournament (TGT) to the learning outcomes matrix class X-G Skills Program RPL SMK Senopati Sedati Sidoarjo?. In accordance with the formulation of the problem, then the purpose of this research is to know is there any influence Cooperative learning model type Teams Games Tournament (TGT) to the learning outcomes matrix class X-G Skills Program RPL SMK Senopati Sedati Sidoarjo. This study is a quasi-experimental design with control grop Nonequivalent design. The study population was all students of class X SMK Senopati Sedati Sidoarjo in Semester II Academic Year 2015/2016 and as samples 59 students are 29 students in grade XG as a class experiment using TGT learning model and 30 graders XF as the control class using conventional methods, Collecting data in this study using a written test. Obtained t > t table (2,757 > 2.00) at the level of 95% which means that H0 rejected and H1 accepted. Thus the test results, we can conclude learning outcomes TGT model is better than the conventional method. In other words, there is the influence of cooperative learning model Teams Games Tournament (TGT) to the learning outcomes matrix class X-G RPL SMK Senopati Sedati Sidoarjo. Keywords : Learning Outcomes, Teams Games Tournament (TGT), Cooperative Learning